Borrowed voices: narrating the migrant's story in contemporary European literature between advocacy, silence and ventriloquism. Issue 2 (3rd April 2019) - Scarabicchi, Caterina
ABSTRACT: Over the last decade, Europe's immigration regulations have raised concerns regarding human rights and divided the public opinion on transnational movement, particularly with the ever-growing number of migrant deaths in the Mediterranean Sea. While the direct voices of migrants themselves are still often absent or marginalised in the debate, numerous European authors have mobilised in favour of a change in policies, portraying migrants' and refugees' stories in their works. This article addresses these complex cultural representations, acknowledging them as essential, albeit ambiguous, acts of solidarity. Drawing on the postcolonial notion of agency, and on the reflections on the representation of suffering subjects in humanitarian narratives, I will consider the cases of the Italian long poem Solo andata (One way only) by De Luca and the French novel Eldorado by Gaudé. While the authors' choice to recreate the migrant's perspective through fiction can be read as a strategy to re-humanise the protagonists of these journeys, I argue that such borrowing of the migrant's story from a non-autobiographical, external viewpoint simultaneously risks further disempowering and silencing them, raising a number of ethical questions on authorship and advocacy whose implications, in literature as in other contemporary media, still remain to be urgently addressed.